Improvement of Phaseolus vulgaris on breastfeeding in female rats - Shiva Roshankhah; Cyrus Jalili; Mohammad Reza Salahshoor (Asian Pacific Journal of Reproduction, 2019)
Objective: To evaluate effect of Phaseolus vulgaris (P. vulgaris) on the breastfeeding in female rats. Methods: This experimental study was done from May 2018 to December 2018 in the Anatomical Department of Medical School in Kermanshah University of Medical Sciences in Iran. In this study, after one-week adaptation and fertilization by male, 40 female rats within 20 days of pregnancy (on average, every mother had 10 newborns) were equally separated into four groups (animals were administrated after delivery of offspring). Group 1 was control group receiving normal saline interaperitoneally, and groups 2, 3, 4 were treatment groups receiving the dose of 20, 50, 100 mg/kg of P. vulgaris interaperitoneally respectively once a day for 60 days. The prolactin hormone was measured by radio immune assay, number and diameter of alveoli via histological and morphometrical examinations, and receptor prolactin gene expression by real-time polymerase chain reaction method. Results: P. vulgaris significantly improved alveoli’s number and diameter, prolactin hormone and receptor prolactin expression when compared to the control group (P<0.001). Conclusions: P. vulgaris is helpful to improve the breastfeeding parameters of rats’ mammary glands.